2021
DOI: 10.3389/fimmu.2021.652488
|View full text |Cite
|
Sign up to set email alerts
|

Acute Alcohol Intoxication Modulates Monocyte Subsets and Their Functions in a Time-Dependent Manner in Healthy Volunteers

Abstract: BackgroundExcessive alcohol intake is associated with adverse immune response-related effects, however, acute and chronic abuse differently modulate monocyte activation. In this study, we have evaluated the phenotypic and functional changes of monocytes in acutely intoxicated healthy volunteers (HV).MethodsTwenty-two HV consumed individually adjusted amounts of alcoholic beverages until reaching a blood alcohol level of 1‰ after 4h (T4). Peripheral blood was withdrawn before and 2h (T2), 4h (T4), 6h (T6), 24h … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…The increased proportions of specific periodontal pathogens caused by ethanol are possibly a result of the decreased commensals (i.e, Lactobacillales , Streptococcus and Rothia ) levels 12 , 44 and/or inflammation-related disturbances (which are expected to act on periodontal pocketing) associated with the immune subversion on the gingival crevicular fluid, ultimately impairing the host-microbial balance. 45 Previous studies also reported impaired neutrophil function 46 and reduced monocyte production of cytokines 47 following alcohol abuse, factors that contribute to increased bacterial proliferation and penetration. This complex interplay sheds light that the association of alcohol intake and periodontitis is driven by a shift in the subgingival microbial composition of those exposed.…”
Section: Discussionmentioning
confidence: 95%
“…The increased proportions of specific periodontal pathogens caused by ethanol are possibly a result of the decreased commensals (i.e, Lactobacillales , Streptococcus and Rothia ) levels 12 , 44 and/or inflammation-related disturbances (which are expected to act on periodontal pocketing) associated with the immune subversion on the gingival crevicular fluid, ultimately impairing the host-microbial balance. 45 Previous studies also reported impaired neutrophil function 46 and reduced monocyte production of cytokines 47 following alcohol abuse, factors that contribute to increased bacterial proliferation and penetration. This complex interplay sheds light that the association of alcohol intake and periodontitis is driven by a shift in the subgingival microbial composition of those exposed.…”
Section: Discussionmentioning
confidence: 95%
“…As CBC lacks the capacity to detect functional shifts in lymphocyte or monocyte subpopulations, future studies utilizing flow cytometry would allow for more extensive characterization of AIE-induced alterations of leukocyte immunoreactivity independent of total number changes. Indeed, much of the existing work examining alcohol effects on blood cells has shown effects on monocyte phenotype ( Janicova et al, 2021 ) or has investigated changes in human subjects with a history of AUD. These studies, while very informative, are often complicated by the poor diet ( Cummings et al, 2020 ), sedentary behavior, and other high-risk behaviors engaged by individuals with AUD, suggesting that adolescent alcohol exposure alone may not be the driving cause for many of the hematological complications associated with heavy alcohol use.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, heavy alcohol consumption patterns are associated with abnormalities in RBC morphology, reduced platelet levels, and reduced WBC levels ( Ballard, 1997 ). While acute alcohol intoxication has been shown to alter monocyte populations, ultimately resulting in a decreased immune response to LPS challenge ( Mandrekar et al, 2009 ; Janicova et al, 2021 ), chronic alcohol exposure sensitizes monocytes to LPS ( Mandrekar et al, 2009 ). Chronic alcohol consumption also changes lymphocyte function, reducing both B ( Sacanella et al, 1998 ) and T cell ( Percival and Sims, 2000 ) levels as well as altering their activation (see Pasala et al, 2015 for relevant review).…”
Section: Introductionmentioning
confidence: 99%
“…Such evidence should guide resource Schematic to interventions on alcohol consumption for those disadvantaged. Although there is no clear evidence suggesting a dysbiotic subgingival microbial profile in those exposed (Oliveira et al 2023), the relationship between alcohol intake and periodontitis seems to be explained by immune subversion on the gingival crevicular fluid due to impaired proinflammatory cytokine release (Janicova et al 2021) and decreased alveolar bone quality (Frazão et al 2020). Those of lower SEP are suggested to be more vulnerable to such a relationship due to the accumulation of adverse exposures that synergistically increase the likelihood of both alcohol harm and periodontitis and/or due to exposure to poor-quality beverages and binge drinking that increases the probability of periodontitis, even when the volume of consumption is the same of those of higher SEP. From a biological point of view, such a scenario may be explained as a result of the allostatic load—the “wear and tear” on the body associated with immune responses to chronic stress—on those of lower SEP.…”
Section: Discussionmentioning
confidence: 99%